The Criticism of Social Justice in Economic Gap - Yapiter Marpi; Erlangga Erlangga (Insignia: Journal of International Relations, 2021)
This research paper examines the dynamics of economic inequality problems facing Indonesia today, especially due to the impact of the Covid-19 Pandemic which hinders the progress of general welfare throughout the country. The difficulty of making breakthroughs to create social justice by Pancasila and the 1945 Constitution can be realized. The purpose of this paper is to examine and analyze the criticality of social justice in economic disparities in society. The research method of this paper uses a description of qualitative analysis supported by secondary data through primary data collection of the sociology of justice, processing of deductive-inductive comprehensive analysis. The conclusion of this paper is the complex problems faced by the country regarding economic inequality caused by non-natural disasters of the pandemic so that social justice is critical in the community, let alone the continuing increase in poverty that cannot be avoided anymore. This research concludes the need for physical development to improve norms and uphold the principles of justice for the realization of a justice facing and the practice of Pancasila as well as increasing welfare for Indonesian citizens equally.